Pregnancy experience among street-involved youth: scope review - Settecerze Rodrigues, Fernanda (2024)
This study aimed to carry out a scope review on the pregnancy experience among street-involved youth, investigating associated risk and protective factors. Paired reviewers independently assessed the retrieved records in a two-step screening process, with data from 28 studies extracted and classified into an evidence protocol from which the results were descriptively analyzed. Risk factors related to a history of abuse and violence, lack of contraception and condoms, and substance use were identified. Furthermore, protective factors related to future aspirations and the role of the support network were identified, providing emotional and financial support, also contributing to the adoption of healthier behaviors and assistance in caring for the baby. The protective potential of social assistance and health institutions that act in line with the sexual and reproductive rights of street youth is discussed.